1984
DOI: 10.1111/j.1600-0773.1984.tb01975.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Affinity of Manganese

Abstract: The melanin affinity of manganese was studied in vitro using melanin isolated from beef eyes or human hair, and synthetic dopamine melanin, which is known to be structurally similar to the melanin present in the pigmented nerve cells in the human substantia nigra. In addition, the uptake of manganese in melanin containing tissues in vitro and in vivo was studied by whole body autoradiography. Manganese was bound to beef eye, human hair and synthetic dopamine melanin, and was taken up in pigmented tissues in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 21 publications
0
34
0
1
Order By: Relevance
“…[40] Its role in the accumulation and release of metal cations in vivo, such as Prospective Article calcium, [7,41] copper, [42] zinc, [42,43] manganese, [44] iron, and other metals, [42,45,46] has received great attention, too. The uranyl oxycation has been used to reveal, by scanning electron microscopy (SEM), the presence of eumelanin deposited on carbon-based electrodes in supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…[40] Its role in the accumulation and release of metal cations in vivo, such as Prospective Article calcium, [7,41] copper, [42] zinc, [42,43] manganese, [44] iron, and other metals, [42,45,46] has received great attention, too. The uranyl oxycation has been used to reveal, by scanning electron microscopy (SEM), the presence of eumelanin deposited on carbon-based electrodes in supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The functional groups associated with these molecular building blocks are central to the metal coordinating abilities exhibited by melanins. 4,7,[18][19][20] In situ, with the exception of NM, melanin is generally deposited in melanosomes, specialized organelles in pigment generating cells. Similar to most cellular organelles, melanosomes are membrane-bound structures containing a variety of molecular species, including lipids, proteins, and melanin.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, rats do not demonstrate selective manganese accumulation in the striatum (8). Another possible explanation for this primate-selective effect is the observation that manganese has a high affinity for neuromelanin and that its deposition is highest in melanin-containing tissues (39). Neuromelanin levels increase considerably with higher phylogeny, and brain levels are highest in the primate brain regions in which the dopaminergic pathways are most active (41 Studies with MPTP have demonstrated that astrocytes play a critical role in neuronal injury through their ability to convert innocuous compounds into a toxic metabolite (16).…”
Section: Introductionmentioning
confidence: 99%